2006
DOI: 10.2337/db06-0600
|View full text |Cite
|
Sign up to set email alerts
|

IL6 Gene Promoter Polymorphisms and Type 2 Diabetes

Abstract: Several lines of evidence indicate a causal role of the cytokine interleukin (IL)-6 in the development of type 2 diabetes in humans. Two common polymorphisms in the promoter of the IL-6 encoding gene IL6, ؊174G>C(rs1800795) and ؊573G>C (rs1800796), have been investigated for association with type 2 diabetes in numerous studies but with results that have been largely equivocal. To clarify the relationship between the two IL6 variants and type 2 diabetes, we analyzed individual data on >20,000 participants from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 25 publications
4
62
1
10
Order By: Relevance
“…Here, we focused on the association between the IL-6 gene −572 C/G polymorphism and T2DM risk due to the scarcity of studies on other SNPs of the IL-6 gene. In 2006, Huth et al (2006) performed a meta-analysis mainly based on unpublished studies and showed that the IL-6 gene −572 C/G polymorphism was not associated with T2DM risk. By comparison, the present meta-analysis obtained a conclusion inconsistent with that study.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we focused on the association between the IL-6 gene −572 C/G polymorphism and T2DM risk due to the scarcity of studies on other SNPs of the IL-6 gene. In 2006, Huth et al (2006) performed a meta-analysis mainly based on unpublished studies and showed that the IL-6 gene −572 C/G polymorphism was not associated with T2DM risk. By comparison, the present meta-analysis obtained a conclusion inconsistent with that study.…”
Section: Discussionmentioning
confidence: 99%
“…171,172 The C allele of one polymorphism in the IL6 promoter, ÀG174C, has in different populations been associated with obesity and decreased risk of T2DM. [173][174][175][176] The C allele results in lower IL6 expression. 177 Furthermore, the CÀ174C genotype has been associated with lower energy expenditure and lower rate of whole-body glucose uptake.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 99%
“…39 O estresse crônico provocado no sistema imunitário pode ocasionar o declínio da sensibilidade à insulina, contribuindo para o desenvolvimento da DM2. 40,41 Excesso de TNF-α, por exemplo, induz diminuição sistêmica na produção de receptores para insulina, que contribui para um estado de resistência à ação do hormônio. 42 Esse mecanismo pode explicar a resistência insulínica observada na obesidade, uma vez que a massa gorda secreta TNF-α.…”
Section: Il-6 E Diabetes Mellitus Tipo 2 (Dm2)unclassified
“…44 E quando comparados os níveis de IL-6 entre pacientes diabéticos e normais, os estudos mostram valores maiores de IL-6 sérica para os portadores da patologia. 33,41,45 Sob o aspecto genético, a presença de SNPs na região promotora do gene da IL-6 sugere que certos alelos podem ser considerados fatores de risco para o desenvolvimento da DM2. 30 A distribuição dos genótipos da IL-6 é significativamente diferente entre indivíduos diabéticos e não-diabéticos, pois o genótipo GG é predominante em pacientes portadores de DM2, quando comparados com pacientes não-diabéticos.…”
Section: Il-6 E Diabetes Mellitus Tipo 2 (Dm2)unclassified